The Irish potato famine pathogen Phytophthora infestans translocates the CRN8 kinase into host plant cells. - Mireille van Damme; Tolga O Bozkurt; Cahid Cakir; Sebastian Schornack; Jan Sklenar; Alexandra M E Jones; Sophien Kamoun (PLoS Pathogens)
Phytopathogenic oomycetes, such as Phytophthora infestans, secrete an arsenal of effector proteins that modulate plant innate immunity to enable infection. We describe CRN8, a host-translocated effector of P. infestans that has kinase activity in planta. CRN8 is a modular protein of the CRN effector family. The C-terminus of CRN8 localizes to the host nucleus and triggers cell death when the protein is expressed in planta. Cell death induction by CRN8 is dependent on its localization to the plant nucleus, which requires a functional nuclear localization signal (NLS). The C-terminal sequence of CRN8 has similarity to a serine/threonine RD kinase domain. We demonstrated that CRN8 is a functional RD kinase and that its auto-phosphorylation is dependent on an intact catalytic site. Co-immunoprecipitation experiments revealed that CRN8 forms a dimer or multimer. Heterologous expression of CRN8 in planta resulted in enhanced virulence by P. infestans. In contrast, in planta expression of the dominant-negative CRN8(R469A;D470A) resulted in reduced P. infestans infection, further implicating CRN8 in virulence. Overall, our results indicate that similar to animal parasites, plant pathogens also translocate biochemically active kinase effectors inside host cells.